Knowledge and Attitude of Future Health Care Professionals towards Pain in Central Saudi Arabia - Al Hossan, Abdulaziz; wajid, Syed; Ghazi, Abdulrahamen; Alrubayi, Faris Fahad; Alwadai, Awad Salam; Babelghaith, Salmeen Doagel; Nasir saud Al Arif, Mohamed (Indian Journal of Pharmacy Practice)
Background: Pain is one of the major reasons why people seek health care. Knowledge deficit and negative attitude are major contributing factors in assessment of pain. The aim of this study was to examine the final year pharmacy students’ knowledge and attitude towards pain management. Method: A cross-sectional survey using a self-completed paper-based survey was conducted on undergraduate final year pharmacy students of King Saud University (KSU), Saudi Arabia (SA). Results: A total of 60 pharmacy students answered the questionnaire (response rate, 85.0%). The overall percentage of correct answer was 42.25%. Half of respondents believed that patient may sleep in spite of severe pain. Approximately, 53.0% of respondents thought that patients are poor judges of their pain. About 60 to 70% of respondents answered 4 questions correctly, mainly related to the pharmacologic pain management which included the preferred route administration of opioid, the appropriate drug for the treatment of cancer pain, and side effect of opioid. Only 10.0% of respondents knew the recommended route of administration of opioid analgesic for patient cancer. Conclusion: The pharmacy students at KSU have inadequate knowledge and negative attitude regarding pain management. Saudi education authorities should modify curricula related to pain management in medical school.
Keywords: Knowledge; Attitude; Pharmacy students; Pain; Saudi Arabia; Management